Wavelet compression and transmission of deformable surfaces over networks - Lopes, A. C.; Gamito, M.; Dias, J. M. S. (Actas do 10º Encontro Português de Computação Gráfica, 2022)
An animation of a deformable surface with fixed topology is formed by a set of connected points (particles), which follow a trajectory over time. The transmission of such an animation is a task that consumes large amounts of bandwidth, as the position of each particle, in each time instant, needs to be transmitted. We propose a wavelet-based compression and streaming mechanism that allows the minimization of the size of the animation data, hence decreasing the total transmission time. The proposed transmission scheme, based on the time-localized feature of the wavelet transform, will be able to stream the animation so that a receiver can immediately view the fraction of the animation received while wavelet coefficients are still arriving.